Organising innovation: unions,young workers and precarity - Simms, Melanie; Holgate, Jane; Hodder, Andy (London, 2018)
"By and large, young people are not particularly negative about trade unions. Research in many countries rejects some of the stereotypes that young people are more individualistic than previous generations and care less about inequality, social issues and employment. Rather, young people often don’t know very much about trade unions. In fact, they often don’t know very much about work and employment in general. So their early experiences of the labour market tend to shape their understanding and expectations. "